0642 Characterizing Actigraphy-Measured Sleep Disturbance in Veterans and Service Members with Post-traumatic Headache following Mild Traumatic Brain Injury. (25th May 2022) - Li, Yihan; Rau, Holly; Engle, Conner; Gunn, Heather; Raskind, Murray; Mayer, Cynthia
Abstract: Introduction: Post-traumatic headache (PTH) frequently occur following traumatic brain injury (TBI) is particularly prevalent in Veterans with deployment-related TBI. PTH is associated with a range of physical and mental health symptoms, including post-traumatic stress disorder (PTSD), depression, anxiety, post-concussive symptoms, and subjective sleep complaints. Subjective sleep disturbance is associated with greater pain severity, and headaches (HA) are associated with poorer sleep. Poor sleep may be a mechanism by which PTH exerts both direct and indirect effects on health outcomes Despite the high prevalence of sleep problems in individuals with PTH, we know little about sleep disturbance in Veterans and military personnel with PTH. This study sought to characterize the relationship between objective sleep disturbance and HA in Veterans and military personnel with chronic PTH following mild TBI. Methods: Veterans and active-duty service members (N=39, Mage= 49.4, 89.7% male) were included from a larger study evaluating prazosin as prophylactic treatment for persistent PTH. Participants completed baseline measures of PTSD symptoms, insomnia, sleep quality, HA frequency and impairment, as well as 7-day actigraphy, sleep diary, and HA logs. Actigraphy-derived sleep parameters include sleep onset latency (SOL), total sleep time (TST), sleep efficiency (SE), and wake after sleep onset (WASO). Daily HA logs were used to assess HA severity and duration. Analyses were conducted in SPSS 26.0 using multilevel modeling, controlling for the effects of time. Results: Preliminary results suggest number of HA days at baseline was significantly associated with self-reported sleep quality (r=-.398, p= .016), but not with subjective SOL, TST, or WASO. Number of HA days was significantly correlated with actigraphy-measured WASO (r=.178, p=.003). Actigraphy-measured SOL, SE, WASO, and TST were not significantly associated with same-day HA severity and duration. Conclusion: This preliminary data suggest examination of sleep fragmentation may be important in enhancing our understanding of PTH and related impairment. Findings support the importance of using both subjective and objective measures in the assessment of sleep in Veterans and service members with PTH. Support (If Any): This project was supported by a VA Career Development Award 5IK2RX001136 from the United States Department of Veterans Affairs Rehabilitation Research and Development Service. The contents of this work do not represent the views of the Department of Veterans Affairs or the United States government.